Intraocular lens calculations in atypical eyes. - Siddiqui, Aazim A.; Devgan, Uday (Indian Journal of Ophthalmology, 2017)
Cataract surgery is the most performed surgical procedure in the field of ophthalmology. The process of intraocular lens (IOL) calculations is a critical step to achieving successful outcomes. Many IOL formulae exist to guide surgeons through the difficult process of picking the most appropriate lens to achieve a certain target refraction. However, these formulae reach within 0.50 diopters of the target refraction only 75% of the time, leaving 25% of the eyes with a significant refractive surprise. A literature review was performed to investigate all the relevant published material on the history, progress, and recent advancements of IOL calculations. Based on this review, the appropriate history, evolution, progress, limitations, and recent advancements are analyzed and explained. Although the modern IOL formulae and biometric devices perform well for average eyes, they are suboptimal for eyes with atypical biometric parameters and also those that are postrefractive and keratoconic. There has not been a single, perfect formula that can resolve the complexities of this process. Various methods of formula optimization and newer generation of IOL formulae and devices may hold the key to improving outcomes in both typical and atypical eyes. These solutions minimize refractive error by introducing new input parameters and complex mathematical techniques to better estimate postoperative lens position.